Task-Test: what lies beyond implementing a task-based assessment? Comparing learners' performance and unveiling learners' perception in a testing situation - Farias, Priscila Fabiane (2014)
Dissertação (mestrado) - Universidade Federal de Santa Catarina, Centro de Comunicação e Expressão, Programa de Pós-Graduação em Inglês: Estudos linguísticos e Literários, Florianópolis, 2014.